The role of the wife in interpersonal communication to the harmony of the Indonesian Fisherman's Family - A.B, Syamsuddin; Mohd. Nor Shahizan Ali,; Fakhri Yusuf, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The dual role of the fisherman's wife requires interpersonal communication in interaction. As a housewife, she also helps her husband work to meet family needs while maintaining family togetherness and honour. The research aims to know the role and function of a housewife in family interpersonal communication. This type of research is qualitative with a communication and sociology approach. The data sources are primary data with 20 key informants, religious leaders, community, and government, each one person, and secondary in the form of books and documents. Data collection methods through interviews, observation, and documentation. As well as theoretical data analysis. The results of the study show that the role of the fisherman's wife is inseparable from interpersonal communication. The part of the wife when the husband goes to sea to catch fish in the sea so that family harmony is created. Namely, a. Maintain household harmony by 1). Assamaturuseng (mutual consensus), 2). Sipakatau (humanize each other), 3). Sipakalebbi Sipakalebbi (glorify/appreciate each other, 4). Sipakinge (advise each other). B. Maintaining honour, namely, 1). Independence; meeting the needs of life with family members; 2). Limit yourself. He was closing himself out of the house, receiving guests, 3). Take care of the children while the husband is at sea. The implication of this paper is to provide advice and affirm policies regarding families living on the coast. Furthermore, it is a reference in social science and communication sociology.